New Approaches to The Study of Fraud In Russia: Challenges of The Economy - The Answer of Science - Oleg DROZDOV; Galina DROZDOVA; Ekaterina DROZDOVA (Communications of International Proceedings, 2022)
Modern Russian economic science pays special attention to research in the field of corporate fraud and fraud in the field of public procurement. The article contains description of the current challenges of the modern Russian economy in terms of detecting and preventing fraudulent activities. The focus of this article is on the construction industry because it plays a crucial role in the spatial development of remote territories. Practical economic and organizational measures are inextricably linked with the theoretical work of Russian researchers. This paper examines various models that attempt to describe the formation of intent to commit fraud, the relationship between the fraudster and the victim as well as identify the signs of manipulation of reports during the construction process. Lastly, this article proposes a model that describes the relationship between the project realization time when the clear intent formation to commit fraud and opportunity could emerge and the actual event of misappropriating assets in an attempt to provide a better understanding of a specific point of time during the realization of the project when the crime can happen in order to timely prevent it.
Keywords: Fraud. Construction. Audit. Corruption.